MARKET REACTION TO THE RATIFICATION OF “RUU IBU KOTA NUSANTARA” - Ingrid Susanto; Giovanni Christiawan Munaiseche; Tarsisius Renald Suganda; Rino Tam Cahyadi (Jurnal Akuntansi Kontemporer, 2026)
Research Purposes. This study aims to analyse the Indonesian capital market’s reaction to the ratification of the “RUU Ibu Kota Nusantara” using abnormal return (AR) and trading volume activity (TVA) on IDX30 companies. Research Methods The study applies an event study approach using the market model and a paired-samples t-test to secondary data from 2022, including daily stock prices, the composite index (IHSG), and trading volume. Research Results and Findings. The findings indicate a significant market reaction on the tenth day prior to the event, characterized by positive AR, suggesting the market's positive anticipation of the bill's ratification. However, during other periods, the market reaction was not significant, implying that the announcement's impact was temporary. For TVA, the paired-samples t-test results reveal a significant difference between the pre- and post-enactment periods, indicating an increase in stock trading volume following the announcement. This study concludes that the enactment of the Nusantara Capital City Bill had a temporary impact on market reaction and increased stock trading volume activity. These findings provide empirical evidence for investors and the government to better understand how significant policies influence the capital market and support more informed investment decision-making.